Hubungan Aktivitas Fisik Dan Pola Makan Dengan Kejadian Stroke Berulang Di RSUD Ahmad Yani Kota Metro - Eka Trismiyana; Dina Sari (Universitas Malahayati Lampung, 2021)
ABSTRACT: CORRELATION BETWEEN PHYSICAL ACTIVITY AND DIET WITH THE INCIDENCE OF RECURRENT STROKES IN AHMAD YANI HOSPITAL METRO CITY IN 2020 Backrgound: Stroke is one of the causes of disability and death. Deaths due to stroke increased by approximately 6 million in 2010 and will become 8 million in 2030. Stroke prevalence data in Indonesia in 2018 is 7.0, increasing to 10.9 ‰. Stroke prevalence data in Lampung Province from 7.7 increased to 10.3 ‰. The percentage of stroke sufferers who experience recurrent strokes is 11.8 - 14.5%. Data from Ahmad Yani Hospital, Metro City for recurrent stroke cases which was quite high in 2019, amounting to 743 cases (29.6%).Purpose: To determine the correlation between physical activity and diet with the incidence of recurrent strokes.Method: This type of research is quantitative. The study design was an observational analytic with a cross sectional approach. The population in this study were all stroke patients at Ahmad Yani Hospital, Metro City, with a total of 62 people. The sampling technique used in this study was accidental sampling. Analysis of the results of statistical tests using the chi square.Results: Most of the respondents had poor physical activity, as many as 33 people (53.2%) and a good diet, as many as 32 people (51.6%). Most of the respondents did not experience recurrent strokes, as many as 34 people (54.8%). The results of the bivariate analysis of physical activity variables (p-value = 0.019, OR = 4.038) and diet (p-value = 0.002, OR = 6). Conclusion: There is a relationship between physical activity and diet with the incidence of recurrent strokes. So it is hoped that health workers are expected to increase public knowledge about recurrent strokes and their relation to the factors that influence it, including diet and physical activity by conducting routine health education. Keywords : physical activity, diet, recurrent stroke INTISARI: HUBUNGAN AKTIVITAS FISIK DAN POLA MAKAN DENGAN KEJADIAN STROKE BERULANG DI RSUD AHMAD YANI KOTA METRO TAHUN 2020 Latar Belakang: Stroke merupakan salah satu penyebab kecacatan maupun kematian. Kematian akibat stroke meningkat kurang lebih 6 juta pada tahun 2010 dan akan menjadi 8 juta di tahun 2030. Data prevalensi stroke di Indonesia tahun 2018 yaitu sebanyak7,0‰, meningkat menjadi 10,9 ‰. Data prevalensi stroke di Provinsi Lampungdari 7,7‰ meningkat menjadi 10,3 ‰. Presentase penderita stroke yang mengalami stroke berulang adalah 11,8 - 14,5%. Data RSUD Ahmad Yani Kota Metrountuk kasus stroke berulang yang cukup tinggi pada tahun 2019 yaitu sebesar 743 kasus (29,6%).Tujuan: Diketahui hubungan aktivitas fisik dan pola makan dengan kejadian stroke berulang.Metode: Jenis penelitian ini adalah kuantitatif. Rancangan penelitian ini adalah analitik observasional dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah seluruh pasien stroke di RSUD Ahmad Yani Kota Metro, dengan jumlah 62 orang. Teknik sampling yang digunakan pada penelitian ini adalah accidental sampling. Analisis dari hasil uji statistik menggunakan chi square.Hasil: Sebagian besar responden memiliki aktivitas fisik yang tidak baik, yaitu sebanyak 33 orang (53,2%) dan pola makan baik, yaitu sebanyak 32 orang (51,6%). Sebagian besar responden tidak mengalami stroke berulang, yaitu sebanyak 34 orang (54,8%). Hasil analisis bivariat variabel aktivitas fisik (p-value = 0,019, OR=4,038) dan pola makan (p-value = 0,002, OR= 6).Kesimpulan: Terdapat hubungan aktivitas fisik dan pola makan dengan kejadian stroke berulang. Sehingga diharapkan petugas kesehatan diharapkan dapat meningkatkan pengetahuan masyarakat tentang stroke berulang serta kaitanya dengan faktor yang mempengaruhinya termasuk pola makan dan aktivitas fisik dengan melakukan penyuluhan kesehatan secara rutin. Kata Kunci : Aktivitas Fisik, Pola Makan, Stroke Berulang